Does Subjective Dietary Knowledge Affect Sugar-Sweetened Carbonated Beverages Consumption and Child Obesity? Empirical Evidence from the Inner Mongolia Autonomous Region in China - Zeqi Liu (International Journal of Environmental Research and Public Health, 2021)
Worldwide, overweight and obesity have become an important public health problem affecting the health of children and adolescents. In China, the prevalence of overweight and obesity has reached 19 percent among the 6–17-year-old age group. Although studies have shown that regular consumption of sugar-sweetened beverages (SSBs), especially sugar-sweetened carbonated beverages (SSCBs), is positively correlated with overweight and obesity among children, the research on ways to reduce SSBs consumption is scarce. This study fills this gap by analyzing data on nearly 4000 students aged between 9–15 from the Inner Mongolia Autonomous Region in China, exploring possible influential pathways between subjective dietary knowledge, SSCBs consumption, and child obesity. The estimation results show that SSCBs consumption significantly mediates the relationship between dietary knowledge and the incidence of overweight and obesity; the mediated effects are different among subgroups. Therefore, improving dietary knowledge related to the lowing of SSBs consumption to reduce the obesity risk may be considered a possible way to reduce the prevalence of overweight and obesity among children.